The relevance of the Social Missions for the development of the Bolivarian Revolution in Venezuela - Scartezini, Natália (Pontifícia Universidade Católica de São Paulo, 2013)
The Bolivarian Social Missions are the major social policy undertaken since the Chavez government’s first term in office. Currently, they are relevant both politically and socially. Their successful implementation made possible the positive evolution of most social indicators, as well as the intensification of the political action of the most marginalized sectors of society. It is for this reason that the analysis of the Social Missions reveals much about the character and the development of the Bolivarian Revolution, making it pertinent to the academic debate. The purpose of this article is thus to point out the principal characteristics and political contributions of these social programs, which closely resemble social movements.